Checklist of Dryinidae (Hymenoptera) from Guangdong Province, China, with descriptions of two new species - Xu, Zaifu; Olmi, Massimo; Guglielmino, Adalgisa; Chen, Huayan (Zootaxa, 2012)
Five subfamilies, 11 genera and 77 species of Dryinidae are listed from Guangdong Province. Two new species, Anteonpteromaculatum Xu, Olmi, Guglielmino & Chen, sp. nov. and Dryinus nanlingensis Xu, Olmi, Guglielmino & Chen, sp.nov. are described from Nanling National Nature Reserve. New synonymies are proposed for Dryinus indicus (Kieffer,1914) (=Chlorodryinus koreanus Móczár, 1983, syn. nov.; Dryinus masneri Olmi, 2009, syn. nov.), Gonatopus nearcticus(Fenton, 1927) (=Acrodontochelys sinensis Olmi, 1984, syn. nov.). Ten species, Anteon atrum Olmi, 1998, A. silvicolumOlmi, 1984, A. viraktamathi Olmi, 1987, Deinodryinus asiaticus Olmi, 1984, Dryinus krombeini Ponomarenko, 1981,Neodryinus sumatranus Enderlein, 1907, Gonatopus malesiae (Olmi, 1984), Gonatopus validus (Olmi, 1984), G. plebeius(Perkins, 1912), and G. asiaticus (Olmi, 1984) are newly recorded from China. Anteon nanlingense Xu, Olmi & He, 2011is newly recorded from Indonesia. Twenty-seven species are newly recorded from Guangdong Province. Ten species, including new ones, are known from Guangdong Province only.